Disturbance type influences plant community resilience and resistance to Bromus tectorum invasion in the sagebrush steppe. Issue 3 (13th March 2018) - Seipel, Tim; Rew, Lisa J.; Taylor, Kimberley T.; Maxwell, Bruce D.; Lehnhoff, Erik A.
Abstract: Question: How does type of disturbance alter plant community composition when an invasive species with high intrinsic population growth rate is present? The sagebrush steppe is a cold semi‐arid steppe dominated by the native shrub Artemisia tridentata Nutt., native bunchgrasses, and has been invaded by the non‐native winter annual Bromus tectorum L. Location: Sagebrush steppe, Montana, USA. Methods: We assessed the effect of fire and soil disturbance, due to bulldozing to create a firebreak, on the resilience of plant communities and their resistance to invasion by B. tectorum . Plant species richness and species composition were monitored for 3 years at two sites post‐fire and firebreak construction. Results: Burned plant communities were resilient and had similar native grass cover and native species richness compared with the unburned sites after 3 years. Soil disturbance from firebreak construction resulted in species composition that was distinct and had lower native grass cover. Type of disturbance also affected the community's resistance to B. tectorum . Bromus tectorum cover was similar in burned and unburned areas, but increased up to three times and remained high where soil disturbance occurred, suggesting a shift to an alternative state. Conclusion: In this northern portion of the sagebrush steppe, communities with native plant cover were resilient to fire but not soil disturbance, which facilitated B. tectorum increase and a transition to an alternative state. In areas of high native plant cover, management tactics should avoid soil disturbance. Abstract : Soil disturbance lessened resilience and increased Bromus tectorum invasion in the sagebrush steppe of North America. Where fire occurred, plant communities were resilient, and resistant to B. tectorum invasion, like unburned communities. Soil disturbance resulted in plant communities in a novel state and should be minimized to prevent B. tectorum invasion.